Simulation Analysis of Ac/Dc Adapter Under Zero No-Load Power Consumption using Simulink Process - Dona Maria Mathew; K. Vinoth Kumar; Nithin.T. Abraham; Vicky Jose (Institute of Advanced Engineering and Science, 2014)
The burst-mode control is generally used to regulate the output voltage of the ac/dc adapter under light or no-load condition. Although the burst-mode control reduces the switching loss, the control-IC and the feedback circuit at the output side still consume a large amount of power. In order to further reduce the power consumption at no-load condition, a zero no-load power (ZNP) ac/dc adapter for electronic equipment with an embedded battery is proposed in this paper. When the proposed adapter is load connected, the operation is same as that of the conventional adapter. At no-load condition, the adapter is totally turned off. As a result the adapter can reduce the no-load power consumption to less than 1mW. Simulation of a 65 W adapter is presented in order to verify its validity.DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.5669